1990
DOI: 10.4315/0362-028x-53.7.550
|View full text |Cite
|
Sign up to set email alerts
|

Surface-adherent Growth of Listeria monocytogenes is Associated with Increased Resistance to Surfactant Sanitizers and Heat

Abstract: Surface-adherent microcolonies of Listeria monocytogenes were obtained by growing cells on glass slides immersed in a low nutrient medium containing excess glucose. The susceptibility of the adherent populations to benzalkonium chloride (100, 400, and 800 ppm solutions), anionic acid sanitizer (200 and 400 ppm solutions), and heat (55 and 70°C) was determined. Adherent microcolony cells decreased by 2 to 3 log cycles immediately after exposure to the sanitizers. The remaining population of microcolony cells su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
0
14

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(215 citation statements)
references
References 0 publications
6
192
0
14
Order By: Relevance
“…Compared with their planktonic counterparts, attached bacteria typically exhibit enhanced resistance to antimicrobial agents (Brown and Gilbert, 1993), biocides (Blenksinsopp et al, 1992), and heat (Frank and Koffi, 1990). Studies have demonstrated the resistance of biofilms of bacteria such as Escherichia coli towards cetrimide (Evans et al, 1990), or Burkholderia cepacia and Serratia marcescens towards biguanides (Marrie and Costerton, 1981;Pallent et al, 1983), isothiazolones and quaternary ammonium compounds (Costerton and Lashen, 1984).…”
Section: Limited Diffusion Through the Biofilmmentioning
confidence: 99%
“…Compared with their planktonic counterparts, attached bacteria typically exhibit enhanced resistance to antimicrobial agents (Brown and Gilbert, 1993), biocides (Blenksinsopp et al, 1992), and heat (Frank and Koffi, 1990). Studies have demonstrated the resistance of biofilms of bacteria such as Escherichia coli towards cetrimide (Evans et al, 1990), or Burkholderia cepacia and Serratia marcescens towards biguanides (Marrie and Costerton, 1981;Pallent et al, 1983), isothiazolones and quaternary ammonium compounds (Costerton and Lashen, 1984).…”
Section: Limited Diffusion Through the Biofilmmentioning
confidence: 99%
“…A biofilm is an assemblage of microbial cells that is irreversibly associated with a surface and enclosed in a matrix of primarily polysaccharide material (7). It has been well documented that microorganisms colonizing surfaces as part of a biofilm are more resistant to environmental challenges than their planktonic counterparts in suspension (10).…”
mentioning
confidence: 99%
“…Nessas condições, os resultados da literatura deixam claro que a eficácia dos desinfetantes, aplicados tanto à microbiota natural quanto à cepas de microrganismos artificialmente inoculadas em superfícies de frutas e verduras, é muito menor do que nos testes de suspensão. Além disso, mesmo que a característica de resistência das cepas aos diferentes princípios ativos dos desinfetantes seja similar, as diferenças nas características de adesividade e formação de biofilmes podem interferir na eficácia dos desinfetantes [1,13,20,23,27,29,35,37,45] Outro fator importante a considerar é o fato de desinfetantes com o mesmo princípio ativo, porém, de marcas comerciais distintas, apresentarem diferença na eficácia antimicrobiana [17]. Assim, é imprescindível o monitoramento periódico da qualidade dos produtos disponíveis no mercado, para garantir segurança dos tratamentos de desinfecção aplicados.…”
Section: Resistência Aos Sanitizantesunclassified